Pengaruh Jarak Tanam dan Pupuk N,P,K terhadap Pertumbuhan dan Hasil Garut (Maranta arundinacea L.) - Anggun Anggun; Supriyono Supriyono; Jauhari Syamsiyah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Arrowroot able to be alternative food because it has high enough carbohydrate content. The increase of productivity of arrowroot can be reached by using plant spacing and fertilization. This study aims to determine the effect of plant spacing and fertilization, also their interaction on growth and yield of arrowroot (Maranta arundinacea L.). This research was held from March to November 2016 in the experimental land, Faculty of Agriculture, Sebelas Maret University. This research arranged in Completely Randomized Block Design (CRBD) consisted of 2 factors; dosage of N,P,K fertilizer (with 3 levels) and plant spacing (with 2 levels). Each treatment was repeated 4 times. The data obtained analyzed with analysis of variance and followed with Duncan Multiple Range Test at 5% level if any significant influences. The results showed that the interaction between plant spacing of 30x40 cm and urea, Sp36 and KCl 300Kg-1ha significantly increased the number of tillers and diameter of arrowroot respectively. The use of plant spacing 30x40 cm tends to increase growth and better yield. The use of 300 Kg-1ha Urea, SP36 and KCl fertilizer significantly increased plant height, while 150 Kg/ha urea, SP36 and KCl fertilizer significantly increased the number of tuber crops.